Fashion illustration of the 16th - 20th cc.: origin, development, functions - Бальвас, Іван (Київський національний університет імені Тараса Шевченка, 2017)
The article deals with the history of fashion illustration as a special genre of art - from its origins to the late 20th century. The author focuses his attention on the life and work of fashion illustrators of the 16th-20th centuries: their common features, creativity and their artistic manner. Several research methods are applied, including hermeneutic and semiotic analysis, synergistic and multidisciplinary approach. Both biographical and typological methods were applied as well.  Key stages of the fashion illustration development are reviewed in the article. It is shown that the fashion illustration changed significantly if not dramatically in order to match the demands of epoch and fashion. The author argues that the fashion illustration should be considered as a separate branch of fine art. He pays special attention to the contribution of the fashion illustrators and designers in the fashion industry development. The paper may be of interest for historians of fashion, fashion editors, designers, who will be able to find useful information, inspiration and new ideas.

У статі розглядається історія модної ілюстрації як особливого жанру образотворчого мистецтва від витоків до першої половини 20-го ст. Головний акцент зроблено на висвітленні життя й творчості модних ілюстраторів 16-20-го ст.: спільні ознаки стилю, характерні особливості творчості, художню манеру. У статті розкрито ключові етапи становлення модної ілюстрації, яка впродовж свого існування кардинально змінювала власний вигляд, призначення та функції відповідно до конкретної мистецької епохи і розвитку моди. Значну увагу приділено аргументації на користь утвердження моди як окремого виду мистецтва У якості дослідницької задачі автором була здійснена спроба оцінити значення модної ілюстрації та її творців в історії модної індустрії. Основні висновки дослідження спрямовані на утвердження модної ілюстрації як окремого жанру образотворчого мистецтва і доведення рівноцінного, вагомого значення для історії моди як модельєра-дизайнера, так і художника-ілюстратора.
Модна ілюстрація XVII – XX ст.: ґенеза, еволюція, функції
Keywords: fashion illustration; haute couture; illustrator; designer; модна ілюстрація; haute couture; художник-ілюстратор; модельєр